Association between Type of Sedation and the Adverse Events Associated with Gastrointestinal Endoscopy: An Analysis of 5 Years' Data from a Tertiary Center in the USA - Basavana Goudra; Ahmad Nuzat; Preet Mohinder Singh; Anuradha Borle; Augustus Carlin; Gowri Gouda (Korean Society of Gastrointestinal Endoscopy, 2017)
Background/Aims The landscape of sedation for gastrointestinal (GI) endoscopic procedures and the nature of the procedures themselves have changed over the last decade. In this study, an attempt is made to analyze the frequency and etiology of all major adverse events associated with GI endoscopy. Methods All adverse events extracted from the electronic database and local registry were analyzed. Although the data analysis was retrospective, the adverse events themselves were documented prospectively. These events were evaluated after subdivision into propofol-based anesthesia and intravenous conscious sedation groups. Results Cardiorespiratory events, including cardiac arrest, were the most common adverse events during esophagogastroduodenoscopy, while bleeding was more frequent in patients undergoing colonoscopy. Pancreatitis was the most frequent adverse event in patients undergoing endoscopic retrograde cholangiopancreatography. The frequencies of most adverse events were significantly higher in patients anesthetized with propofol. Automatic regression modeling showed that the type of sedation, the American Society of Anesthesiologists physical status classification, and the procedure type were some of the predictors of immediate life-threatening complications. Conclusions Clearly, our regression modeling suggests a strong association between the type of sedation as well as various patient factors and the frequency of adverse events. The possible reasons for our results are the changing demographics, the worsening comorbidities of the patient population, and the increasing technical complexity of these procedures. Although extensive use of propofol has increased patient satisfaction and procedure acceptability, its use is also associated with more frequent adverse events.